ANN and ANFIS Approaches to Calculate the Heating and Cooling Degree Day Values: The Case of Provinces in Turkey - Isik, Erdem; Inalli, Mustafa; Celik, Erkan (Springer Heidelberg, 2019)
Energy analysis plays a vital role in developing an optimum and cost-effective design for the heating, ventilating and air conditioning system of a building. The values of heating degree days (HDD) and cooling degree days (CDD) are used to analyze the demand for energy for buildings. In this study, the HDD and CDD values for Turkey were calculated using estimated temperature values. An artificial neural network (ANN) and an adaptive network-based fuzzy inference system (ANFIS) were applied for the estimation of temperature values. The Levenberg-Marquardt training algorithm was used for the feedforward backpropagation of the ANN, whereas the Sugeno-type fuzzy inference system was used for the ANFIS. Meteorological data from the last 11years were used for the proposed approaches, and these were applied to different stations (n=50) of the Turkish State Meteorological Service. In relation to the insulated building design, base temperatures have been considered as 16 degrees C and 18 degrees C for the HDD and 22 degrees C and 24 degrees C for the CDD based on a literature review. Two novel maps were prepared for the CDD and HDD. The calculated degree days and the maps are consistent with those from the Turkish State Meteorological Service.
Keywords: Heating degree days; Cooling degree days; ANN; ANFIS; Turkey